2018
DOI: 10.1007/978-981-13-1435-3_6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IGF-1 Signaling in Skeletal Muscle Atrophy

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 162 publications
1
45
0
Order By: Relevance
“…Conditional Cre ablation of satellite cells has led to mixed results and views on the role of satellite cell participation in the muscle growth response to overload that results from ablation of synergistic muscles (Egner et al, 2016;Lee et al, 2012;Murach et al, 2017). Among the best-described molecular mechanisms behind the control of muscle size are the insulin-like growth factor 1, transforming growth factor beta and myostatin signalling pathways (reviewed in Lee, 2004;Chen et al, 2016;Timmer et al, 2018) (see poster). Inhibition of myostatin has a dramatic effect on muscle size (Lee and McPherron, 2001), although the cellular mechanisms involved are uncertain.…”
Section: Hypertrophy Of Skeletal Musclementioning
confidence: 99%
“…Conditional Cre ablation of satellite cells has led to mixed results and views on the role of satellite cell participation in the muscle growth response to overload that results from ablation of synergistic muscles (Egner et al, 2016;Lee et al, 2012;Murach et al, 2017). Among the best-described molecular mechanisms behind the control of muscle size are the insulin-like growth factor 1, transforming growth factor beta and myostatin signalling pathways (reviewed in Lee, 2004;Chen et al, 2016;Timmer et al, 2018) (see poster). Inhibition of myostatin has a dramatic effect on muscle size (Lee and McPherron, 2001), although the cellular mechanisms involved are uncertain.…”
Section: Hypertrophy Of Skeletal Musclementioning
confidence: 99%
“…Surprisingly, we did not observe an expected decrease in IGF-1 level, but we have found an elevation of the concentration of that particular protein, but only in red muscle. However, some reports show that under certain conditions, like immobilization, muscle denervation [24], or in atrophy models induced by proinflammatory cytokines [25], IGF-1 does not prevent muscle cell atrophy, and its level may stay unaltered.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1/IGF-1R contributes to muscle hypertrophy on untrained state mainly through activating phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt)-mammalian target of rapamycin (mTOR) pathway [16][17][18], evidenced as IGF-1 induced-growth promotion of skeletal muscle could be greatly inhibited by PI3K inhibitor LY294002 or Akt inhibitor KP372-1 [19]. PI3K/Akt-mTOR pathway is activated by phosphorylating PI3K, Akt and mTOR successively after PI3K translocation to phosphorylated insulin receptor substrate 1 [18], then exerted its vital roles in regulating muscle development and hypertrophy by promoting proliferation and muscle protein synthesis and preventing muscle degradation as well [20].…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1/IGF-1R contributes to muscle hypertrophy on untrained state mainly through activating phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt)-mammalian target of rapamycin (mTOR) pathway [16][17][18], evidenced as IGF-1 induced-growth promotion of skeletal muscle could be greatly inhibited by PI3K inhibitor LY294002 or Akt inhibitor KP372-1 [19]. PI3K/Akt-mTOR pathway is activated by phosphorylating PI3K, Akt and mTOR successively after PI3K translocation to phosphorylated insulin receptor substrate 1 [18], then exerted its vital roles in regulating muscle development and hypertrophy by promoting proliferation and muscle protein synthesis and preventing muscle degradation as well [20]. Tight relationship of AR with PI3K/ Akt-mTOR pathway has been revealed by considerable amount of evidences, for example, PI3K/Akt inhibitor significantly reduced testosterone-induced muscle hypertrophy, and in turn, AR antagonist flutamide offset the increase of muscle mass caused by androgen supplementation accompanied with the decreased levels of IGF-1R and p-Akt [21,22], which indicated that androgen/AR-induced muscle hypertrophy in untrained participants was at least partly associated with the activation of IGF-1-Akt/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%